Central nervous system involvement: A rare detour for myeloma cells-case report of an usual presentation! - Shifa Farheen; Abhishek Singh; Poonam Yadav; Preeti Tripathi; Arijit Sen (Journal of Applied Hematology, 2021)
Extramedullary involvement in multiple myeloma (MM) is seen in 7%–18% of cases. The common organs involved are skin and upper respiratory tract. The uncommon organs involved include the liver, spleen, kidney, pleura, lymph nodes, and soft tissue. Central nervous system (CNS) involvement is extremely rare and occurs in only about 1% of patients. We present an interesting case of nonsecretory MM (NSMM) with atypical involvement of the liver, spleen and CNS. An elderly female patient initially presented with low backache. Skeletal survey showed multiple lytic bony lesions. An initial diagnosis of plasma cell neoplasm was made based on the biopsy of the sacral lytic lesion. No monoclonal gammopathy was found in the serum or urine electrophoresis. A diagnosis of NSMM was made and the patient was started on bortezomib, dexamethasone, lenalidomide (VRD regime). However, over the next 2 months or so, the patient was found to have involvement of liver, spleen, and meninges on imaging despite chemotherapy. The plasmablastic lesions were confirmed on liver biopsy, bone marrow, and cerebral spinal fluid study. Patient showed remarkable clinical improvement on addition of daratumumab to the VRD regime and is currently under maintenance therapy. Repeat imaging shows the reduction in lytic lesions. This case is reported as a rare combination of NSMM with CNS involvement.